Women's equality in the era of permacrisis - Koutselini, Mary (Frontiers in Political Science, 2024)
Permacrisis implies a permanent state of crisis, contrasting with polycrisis and intracrisis, which refer to crises in several fields that can be investigated and resolved. Women's equality has been a longstanding issue, analyzed theoretically and through research exploring persistent and pervasive inequality in all areas of life. This study discusses the concept of permacrisis from a gender perspective and presents research highlighting the effects of interconnected crises on women's rights and societal presence. Ongoing crises—economic, environmental, political, and educational—have been exacerbated by temporary wars, climate change, pandemics, and disputes over international institutions for the protection of human rights and the vulnerable populations. These issues, combined with ineffective political leadership, have made women's equality an increasingly distant goal. This situation calls for new analytical frameworks that go beyond the pessimism of permacrisis and lead to what can be termed a meta-crisis, a transcendence of current obstacles. Thus, the main aims of this study are two-fold: First, to discuss permacrisis from a gender perspective, and second, to propose research evidence showing that gender inequality as an inherent aspect of permacrisis requires new theoretical insights for effective analysis.